2020
DOI: 10.3390/mi11040431
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Sensor-Assisted Paper-Based Competitive Lateral Flow Immunoassay for the Rapid and Sensitive Detection of Ampicillin in Hospital Wastewater

Abstract: In this study, a convenient assay method has been developed based on labeled functional nucleic acids (H-DNA) and a competitive fluorescent lateral flow immunoassay (CF-LFI) for ampicillin (AMP) detection. Herein, we designed the tunable AMP probes for AMP detection based on the AMP aptamer, and the secondary DNA fragment. The probes can generate tunable signals on the test line (T line) and control line (C line) according to the concentration of AMP. The accuracy of detection was improved by optimizing the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…e assay had a limit of detection of 3.71 U/ml and correlated with ELISA. A DNA aptamer for residual penicillin antibiotic ampicillin was prepared by Lin and coworkers [51]. e researchers used hexachlorofluorescein for oligonucleotide labeling and were able to detect ampicillin in a range of 10 to 200 ng/l and a limit of quantification of 2.71 ng/l when water sample was analyzed.…”
Section: Current Trends In Lft Construction In Point-of-care Diagnosismentioning
confidence: 99%
“…e assay had a limit of detection of 3.71 U/ml and correlated with ELISA. A DNA aptamer for residual penicillin antibiotic ampicillin was prepared by Lin and coworkers [51]. e researchers used hexachlorofluorescein for oligonucleotide labeling and were able to detect ampicillin in a range of 10 to 200 ng/l and a limit of quantification of 2.71 ng/l when water sample was analyzed.…”
Section: Current Trends In Lft Construction In Point-of-care Diagnosismentioning
confidence: 99%
“…Thus, the next experiment was taken with PBS buffer (pH = 7.4). Furth the concentration of detection probes was another key factor in the accuracy of th In our previous work [27], it was found that 500 nM was the most suitable, so nM of detection probe was chosen in this work.…”
Section: Optimization Of Lfa Assay Parametersmentioning
confidence: 99%
“…Furthermore, the concentration of detection probes was another key factor in the accuracy of the assay. In our previous work [27], it was found that 500 nM was the most suitable, so then 500 nM of detection probe was chosen in this work. To achieve the optimal conditions for the quantitative determination of AMP and KAM, the type of NC membrane, the distances between each test line, the distances between the internal line and the conjugate pad, and the detection time were investigated The capture DNAs were immobilized on their corresponding lines.…”
Section: Optimization Of Lfa Assay Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 40 pharmaceuticals were authenticated in 96-well plates using a seven-sensor colorimetric array [34]. A penicillin antibiotic ampicillin was detected using colorimetric [35][36][37] and fluorimetric [38][39][40] techniques. Aggregational, enzymatic, and immune methods with colorimet-ric detection were developed for another penicillin compound, benzylpenicillin [32,41].…”
Section: Introductionmentioning
confidence: 99%